Justification criteria for Inter-Basin Water Transfer Projects - Laassilia Oussama (EDP Sciences, 2021)
When implemented on a large scale, Interbasin Water Transfer (IBWT) projects are one of the most significant human interventions in natural environmental processes. Although water transfer might have considerable beneficial impacts, it produces inevitably other adverse effects on different levels. The present work aims to assess the phenomenon of IBWT to answer the question of whether such transfers are justified or not. To this end, this paper is first introduced by reviewing criteria proposed by some international organizations and epistemic communities for assessing IBWT. Then, a coherent set of IBWT evaluation criteria are proposed. Afterward, the authors have applied the chosen criteria to the North-South Water Transfer Project (NSWTP) in Morocco to provide a global assessment. The results show that the NSWTP, in its current version, is not justified. To remedy the negative sides of this project, the authors propose to limit the water transfer only between Sebou (donor) and Bouregreg (recipient), all in increasing the storage capacity of the recipient reservoir. On the other hand, studies related to the legal and institutional sides, and the ecological impacts are to be finalized.